Transhumanism in the context of Ethos of enhancement and search for Identity: philosophical origins - Parkhomenko, Yurii (Skhid, 2024)
The article considers the problem of transhumanism in the context of the ethics of enhancement. It is noted that modern experiments on the transformation of human identity, the improvement of physical and intellectual capabilities of a person with the help of modern biotechnologies are just a modification of old idea of self-transcendence, which has always worried humanity. Pre-philosophical versions of human improvement within mythology outlined the horizon of the ethos of enhancement, its main directions. They consisted in ritual attempts to go beyond the constants of human identity: mortality, division into two sexes and intelligence. Accordingly, the foundations were laid for future directions of intellectual thought that comprehend these constants: immortalism, transgenderism and the philosophy of artificial intelligence. It is proved that within the classical tradition of philosophy there are three paradigms (cosmocentric, theocentric and anthropocentric), which, despite their individual characteristics, are based on the common idea of representation and the metaphysical opposition of essence and existence, which must be removed in the eschatological perspective of the “end of history”. In the non-classical tradition, metaphysical ideas of essence and representation are denied, and a new constructivist paradigm is put forward, which becomes the basis for the ethos of enhancement in general and the project of transhumanism in particular. At the same time, the article expresses concern that the constructivist non-classical paradigm, taken as the foundation for the ethical examination of transhumanism, contains significantly more existential risks than the classical representative one.